Association between epidural catheter tip malposition and anesthesiologists' experience after graduation: A cross-sectional study using postoperative CT images. - Mitsuhiro Matsuo; Natsumi Sakamoto; Mariko Takebe; Tomonori Takazawa (PLoS ONE)
Objectives This study aimed to examine the incidence of epidural catheter tip malposition using postoperative CT images, and investigated its relationship with anesthesiologist and patient characteristics. Methods Patients who had undergone epidural anesthesia at our hospital during the previous 18 years, and who had a thorax and abdominal CT scan within 5 days after surgery were included. Malposition was defined if the tip of the catheter did not penetrate the ligamentum flavum in postoperative CT images. Results Among 189 eligible patients (median age 71 years, range 15-89), 78 (41%) were female. The median number of years of postgraduate experience of the physicians inserting the epidural catheter was 5.7 years (range 2.0-35.4). All epidural catheters were inserted using the paramedian approach in the left lateral decubitus position. The puncture site was the middle (48%) or lower (49%) thoracic spine. Epidural catheter malposition was observed in 24 patients (12.7%, 95% confidence interval [CI] 8.3-18.3). Among these cases, catheter tips were located at the vertebrae (vertebral arches: 9, transverse processes: 2, spinous process: 1), in superficial soft tissue (erector spinae: 5, subcutaneous: 4), and in deep soft tissue (intervertebral foramina: 2, subpleural space: 1). Anesthesiologists in the malposition group had significantly more experience since graduation (median 10.1 years vs. 5.6 years, P = 0.010). No other characteristics showed an association with catheter malposition. Conclusions Analysis of postoperative CT images revealed that the epidural catheter tip did not penetrate the ligamentum flavum in approximately 13% of cases. Our results suggest that even experienced anesthesiologists should be vigilant regarding proper catheter tip positioning.